The Chair is a Poetic Symbol in "Al- Kursi" Divan of Sherko Bikas - Younis, Abdullah B.; Abdullah, Hussein A. (Humanities Journal of University of Zakho, 2017)
Modern poetic experiment is abounding in many artistic phenomena. Using symbol is one of these phenomena. So, poets took an interest in utilizing symbol to achieve their goals, represented by reaching to artistic perfection, and ability to communication as well as influence. Shirko Pikah S. is one of poets who utilize the symbol in the poetical works. He tended to this phenomenon since he entered into the world of poetry. Vicissitudes of time greatly changed. Most of these vicissitudes actuated him to utilize the symbol. The more his life prolonged, the more his divans increased. Thus, he had numerous symbols in comparison with the symbols that the other poets had. He utilized the symbol a lot especially in his divan, "Al- Kursi". In his divan, Shirko Pikah S. talked about a chair, since it was a green tree in the plains till it became a piece of wood in the hand of a skillful carpenter, to make many things, such as stick, bed, oar, window, table, shelf, stage, pillars … etc. In this work, a wooden piece was transformed into a chair. We found that Pikah S. listened carefully to the pains and delights of this chair by means of a language full of significances and symbols. Many techniques, such as remembrance, narration and talking about memories that represent a history including human beings and inanimate beings, were also utilized. Hence, he became deep-rooted in his land and adhered to his issue and heritage. He sent his message to the other in order to consider carefully the meanings and goals, and to make him search behind the scenes so that he finds the hidden intention. According to Shirko Pikah S., the symbol is one of the most important stylistic elements that the formation of chair picture is based on. The present study shows how the symbol and the other components are utilized to form the pictures in the literary works.